Quality of life in cancer patients at the end of radiotherapy compared to a general population sample in Germany - Fabian, Alexander; Rühle, Alexander; Liegl, Gregor; Domschikowski, Justus; Trommer, Maike; Ferdinandus, Simone; Becker, Jan-Niklas; Wurschi, Georg; Boeke, Simon; Sonnhoff, Mathias; Grott, Christoph A.; Käsmann, Lukas; et al. (International journal of cancer, 2025)
Germany has one of the highest cancer incidence rates in Europe. Radiotherapy is essential for patients with cancer as 50% have an evidence-based indication for radiotherapy. However, it is unknown how health-related quality of life (HRQoL) of cancer patients undergoing radiotherapy compares to the general population in Germany. Therefore, we conducted a secondary analysis by pooling cross-sectional individual-level data from a multicenter cohort of cancer patients (n = 1052) undergoing radiotherapy across Germany and a normative sample from the German general population (n = 1006). We used the EORTC QLQ-C30 to measure global HRQoL (range: 0-100). Higher scores indicate higher HRQoL. We used ANOVA for univariable and ANCOVA with predefined covariates for multivariable analyses. As per univariable analysis, cancer patients had significantly lower global HRQoL compared with the general population (mean [M] = 54.6 vs. M = 65.9; p < .001). This difference was smaller but persisted in the multivariable analysis (M = 56.5 vs. M = 63.5; p < .001). Multivariable analyses stratified by education showed that HRQoL was only lower in cancer patients with medium (M = 56.2 vs. M = 63.0; p < .001) or high education (M = 57.0 vs. M = 66.5; p < .001) compared with the general population. The minimal important difference threshold of seven points was only met in the group with high education. In conclusion, there may be a meaningful gap in HRQoL of cancer patients at the end of radiotherapy compared with the general population, mainly in patients with higher educational levels. Upon validation, this would highlight the need for supportive care and optimized radiotherapy strategies to eventually close the HRQoL gap.
Gesehen am 20.01.2026